EFEKTIFITAS PENGGUNAAN B AHASA LEMBAK DALAM PENYAMPAIAN MATERI PELAJARAN OLEH GURU PADA SISWA KELAS VII SMP NEGERI 1 TANJUNG TERDANA BENGKULU TENGAH - Dahlia Dahlia (UNIVED PRESS, Universitas Dehasen Bengkulu, 2019)
The problem of this study is how the effectiveness of the use of the Lembak language in the delivery of subject matter by teachers to Class VII Students of Tanjung Tanjung State Junior High School Terdana Bengkulu Tengah. The purpose of this study was to find out in detail the effectiveness of the use of Lembak language in the delivery of subject matter by teachers to Grade VII Students of SMP Negeri 1 Tanjung Terdana Bengkulu Tengah, this study used a descriptive method using a quantitative approach. The population in this study were students in grade VII Tanjung 1 State Middle School There were 117 people in Central Bengkulu. In this study the sample was taken as much as 25% of the population so that the sample amounted to 29 people. Data collection techniques in this study used observation, questionnaire, and documentation techniques. Data analysis techniques were carried out with the help of interpretation based on percentage calculation (proportion interpretation) and using the help of the Likert Scale. The results of the study show an explanation of the subject matter delivered by the teacher through the Lembak language to students in grade VII of Tanjung 1 Middle School SMP Menghana Bengkulu Tengah can be said to be effective. This is based on the results of the average score of 59.59 if consulted with the Likert scale used, the score is in the interval 51-62 in the effective category. The use of Lembak language by the teacher according to respondents can influence the achievement of learning objectives, the subject matter can be understood by students, the material is mastered by students, students have better learning outcomes and students are motivated to learn.